Assessing the Risks to the Japanese Government Bond (JGB) Market - Lam, Waikei (IMF Working Papers; Working Paper ;, 2011)
Despite the rise in public debt, Japanese Government Bond (JGB) yields have remained low and stable, supported by steady inflows from the household and corporate sectors, high domestic ownership of JGBs, and safe-haven flows from heightened sovereign risks in Europe. Over time, however, the market's capacity to absorb new debt will likely shrink as population ages and risk appetite recovers. In the short term, a decline in fund supply from the corporate sector, where financial surpluses are abnormally high, and spillovers from global financial distress could push up JGB yields. Fiscal reforms to reduce public debt more quickly and lengthen the maturity of government bonds will help limit these risks.